TINGKAT KECEMASAN WANITA YANG BERADA PADA MASA DEWASA AWAL DALAM MEMASUKI PERNIKAHAN DI NAGARI MUARA INDERAPURA KECAMATAN AIR PURA KABUPATEN PESISIR SELATAN - Agustin, Meylani Rena; Kasih, Fitria; Yulastri, Weni (Bimbingan dan Konseling, 2013)
In this research, the writer found some Problems based on a phenomena in the field is the women who are anxious to get a couple who can not make ends meet any women who worry about getting at domestic violence (domestic violence), the researchers raised concerns about the level of anxiety research women who are in a period early adulthood in entering marriage in Nagari Inderapura Pura Kecamatan Air Pura Kabupaten Pesisir Selatan. The purpose of this study is to describe: (1) women who are in early adulthood to meet physiological needs, (2) The level of anxiety women who are in early adulthood in meeting the psychological needs. This research is a descriptive study that sought to describe the situation for what it is. The overall study population was adult women who enter marriage early in the Nagari Inderapura Kecamatan Air Pura Kabupaten Pesisir Selatan, techniques used in sampling is total sampling 86 people. The instrument used in this study was a questionnaire, while the percentage of data analysis techniques used. The results revealed that: (1) Rate women who are in early adulthood in meeting the physiological needs as much as 50 % in the high category. (2) The level of anxiety women who are in early adulthood in meeting the psychological needs as much as 87 % in the very high category. Based on the results of the study authors suggest in adult women enter marriage early in order to know and understand what the purpose of a wedding. Business courses so that students knowledge about the professionalism of marriage and further research in order to follow up on these results from a wider aspect.